History of Low Birth Weight and Cigarette Smoke Exposure on the Incidence of Stunting in Toddlers Aged 24-59 Months - Rakhmi Aliffiyah Azhari; Farida Wahyu Ningtyias; leesia Yusi Ratnawati (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Stunting is chronic malnutrition in children under the age of five, especially during the first 1000 days of life, which, if not properly addressed, can increase morbidity and mortality rates. The prevalence of stunting in Jember Regency in 2022 was higher than in East Java (34.9%). So far, several studies on risk factors for stunting have only focused on nutritional issues, but other more complex issues, such as exposure to cigarette smoke, have rarely been studied. The aim of this study was to determine the relationship between a history of Low Birth Weight (LBW) and stunting, and exposure to cigarette smoke and stunting. Cigarette smoke exposure factors included the number of smoking family members, their smoking status, smoking duration, smoking locations, cigarette types, and the number of smoking consumed. This study used a case-control design and was conducted in 3 stunting loci with a sample size of 134, comprising 67 stunting and 67 non-stunting children, matched for sex, age, and area of residence. The sampling technique used was proportional random sampling. Data, were collected using a modified Secondhand Smoke Exposure Scale (SHES) questionnaire, and bivariate analysis with chi-squared and multivariate analysis with logistic regression. The results showed no association between a history of LBW and stunting. However, there was a most significant association between exposure to cigarette smoke and stunting in terms of smoking location and number of cigarettes consumed. It is recommended that health centers address this issue by providing education on the dangers of smoking in the home.